Central nervous system (CNS) prophylaxis in antiCD20-CHOP treated DLBCL at intermediate to high risk for CNS relapse: A systematic review and meta-analysis. (November 2021) - Ho, Guiyi; Tan, Cherie; de Mel, Sanjay; Poon, Limei; Chan, Esther H.L.; Lee, Joanne; Liu, Xin; Chng, Wee Joo; Chee, Yen Lin; Soon, Yu Yang; Jeyasekharan, Anand D.
Graphical abstract: Highlights: CNS prophylaxis is widely used in the treatment of DLBCL but evidence to support this practice is lacking. We performed a systematic review and meta-analysis specifically focusing on antiCD20-CHOP treated DLBCL cases at intermediate to high CNS relapse risk, comparing the outcome of CNS relapse in patients with and without prophylaxis. We found no statistically significant reduction in CNS relapse rates in intermediate/ high risk DLBCL patients who receive CNS prophylaxis with intrathecal or intravenous chemotherapy. The quality of evidence supporting these observations were low to moderate. Abstract: CNS prophylaxis is commonly used in Diffuse Large B-Cell Lymphoma (DLBCL) patients with risk features for CNS relapse. This systematic review and meta-analysis compares CNS relapse rates with and without CNS prophylaxis, for patients at intermediate to high CNS relapse risk. Studies reporting CNS relapse risk category and CNS outcomes with and without CNS prophylaxis for antiCD20-CHOP treated DLBCL patients were included. 10 studies with 3770 patients at intermediate to high CNS relapse risk were analyzed. No significant difference in the pooled Absolute Risk Difference (ARD 0.01, 95 % CI -0.01 to 0.02, P = 0.61) or Risk (RR 1.22, 95 % CI 0.81–1.83, P = 0.34) was noted in patients with and without CNS prophylaxis. There were also no differences within pre-specified subgroups of IV Methotrexate or IT chemotherapy. However, the quality of evidence supporting these observations was low. A meta-analysis of individual patient data will help evaluate the benefit of CNS prophylaxis strategies.